The Genome Sequence of the Eastern Woodchuck (Marmota monax) – A Preclinical Animal Model for Chronic Hepatitis B. Issue 12 (1st December 2019) - Alioto, Tyler S; Cruz, Fernando; Gómez-Garrido, Jèssica; Triyatni, Miriam; Gut, Marta; Frias, Leonor; Esteve-Codina, Anna; Menne, Stephan; Kiialainen, Anna; Kumpesa, Nadine; Birzele, Fabian; Schmucki, Roland; et al.
Abstract: The Eastern woodchuck ( Marmota monax ) has been extensively used in research of chronic hepatitis B and liver cancer because its infection with the woodchuck hepatitis virus closely resembles a human hepatitis B virus infection. Development of novel immunotherapeutic approaches requires genetic information on immune pathway genes in this animal model. The woodchuck genome was assembled with a combination of high-coverage whole-genome shotgun sequencing of Illumina paired-end, mate-pair libraries and fosmid pool sequencing. The result is a 2.63 Gigabase (Gb) assembly with a contig N50 of 74.5 kilobases (kb), scaffold N50 of 892 kb, and genome completeness of 99.2%. RNA sequencing (RNA-seq) from seven different tissues aided in the annotation of 30, 873 protein-coding genes, which in turn encode 41, 826 unique protein products. More than 90% of the genes have been functionally annotated, with 82% of them containing open reading frames. This genome sequence and its annotation will enable further research in chronic hepatitis B and hepatocellular carcinoma and contribute to the understanding of immunological responses in the woodchuck.